Association Between Stability and Urologic Lesions in Pelvic Ring Fractures. A Case Series Report. Issue 7 (9th August 2021) - Corró, Sebastián; Sallent, Andrea; Pons, MD, Aleix; Ares, Óscar; Barastegui, David; Seijas, Roberto
Abstract: Purpose: Pelvic ring fractures represent a subgroup of potentially serious injuries due to the fractures themselves, as well as the associated injuries. In fact, over 4% of cases have concomitant lower urinary tract injuries. The aim of this study was to analyze the relationship between the instability of pelvic ring fractures and the presence of lower urinary tract lesions. Materials and methods: A retrospective review of patients with pelvic ring fractures at our center between 2007 and 2015 was performed. Fractures were categorized according to the Tile classification system. Patients with lower urinary tract lesions were selected and categorized according to the lower urinary tract lesion identified (urinary bladder, urethral or combined). Subsequently, a statistical analysis was carried out to assess the association between these variables. Results: 614 patients with pelvic ring fracture were included, corresponding to 260 (42.3%) men and 354 (57.7%) women. 25 patients (4.1%) were diagnosed of lower urinary tract injury (17 bladder injuries, 8 urethral injuries and 0 combined injuries). Urethral injuries were more frequent among men (1.9% incidence in men vs 0.8% in women). A lower incidence of lower urinary tract lesions was detected in stable pelvic ring fractures (type A, p 0.02). Overall, type C3 showed the highest incidence of lower urinary tract lesions (22.2% incidence, p  = 0.04). Conclusion: In our series, a greater incidence of higher urinary tract injuries was observed in patients with unstable pelvic ring fractures (Tile type B and C) with respect to stable fractures (Tile type A). Therefore, a high index of suspicion should be maintained in order to identify high risk patients.